The help - Stockett, Kathryn (New York Amy Einhorn Books, 2009)
In Jackson, Mississippi, in 1962, there are lines that are not crossed. With the civil rights movement exploding all around them, three women start a movement of their own, forever changing a town and the way women--black and white, mothers and daughters--view one another.
Keywords: Civil rights movements -- Fiction; African American women -- Fiction; Housekeepers -- Mississippi -- Fiction; Jackson (Miss.) -- Fiction